2006
DOI: 10.1590/s0102-311x2006001300002
|View full text |Cite
|
Sign up to set email alerts
|

Use of research results in policy decision-making, formulation, and implementation: a review of the literature

Abstract: This paper offers a critical review of the theo-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
75
0
31

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(107 citation statements)
references
References 31 publications
1
75
0
31
Order By: Relevance
“…First, measurement should involve attempts to separate the effect of research on policy inputs, such as position statements, outputs, such as regulatory change, and outcomes, such as improved air quality or safer public transport (Renkow and Byerlee, 2014;Hazell and Slade, 2014;Gaunand et al 2017;Almeida and Báscolo, 2006). This analytical differentiation is vital to measurement.…”
mentioning
confidence: 99%
“…First, measurement should involve attempts to separate the effect of research on policy inputs, such as position statements, outputs, such as regulatory change, and outcomes, such as improved air quality or safer public transport (Renkow and Byerlee, 2014;Hazell and Slade, 2014;Gaunand et al 2017;Almeida and Báscolo, 2006). This analytical differentiation is vital to measurement.…”
mentioning
confidence: 99%
“…Policy makers have to sell, argue, advocate, and get reelected in light of their available political capital (26). The evidence for a particular action does not necessarily lead to policy change (3,147). Public health agencies often face obstacles from other stakeholders in proposing or implementing new evidence-based practices.…”
Section: Political Challengesmentioning
confidence: 99%
“…Prior study has indicated that the policy making and research processes are heavily influenced by context (Rü tten et al 2003;Almeida and Báscolo 2006;Contandriopoulos et al 2010), and that policy making setting may be a factor in research utilization (Weiss 1978;James and Jorgensen 2009). In this study, we developed a conceptual framework to evaluate context, content, and rationale of the policy process simultaneously (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Use of research data in policy making has previously been characterized as instrumental (i.e., direct, actionable), conceptual (i.e., diffuse, gradually enlightening), or symbolic (i.e., strategic, tactical) (Pelz 1978;Weiss 1979;Trostle, Bronfman, and Langer 1999;Hanney et al 2003;Almeida and Báscolo 2006). We explore the symbolic use of research evidence.…”
mentioning
confidence: 99%